2013
DOI: 10.1371/journal.pone.0064648
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Porcine Cytomegalovirus (PCMV) in Sichuan Province, China: 2010–2012

Abstract: Porcine cytomegalovirus (PCMV) is an immunosuppressive virus that mainly inhibits the immune function of the macrophage and T-cell lymphatic systems, and has caused huge economic losses to the porcine breeding industry. Molecular epidemiological investigation of PCMV is important for prevention and treatment, and this study is the first such investigation in Sichuan Province, Southwest China. A PCMV positive infection rate of 84.4% (865/1025) confirmed that PCMV is widely distributed in Sichuan Province. A phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Phylogenetic analysis based on the complete DPOL gene nucleotide sequences demonstrated that all the PCMV isolates share very close relationship, belonging to the same cluster together with HHV-6 and HHV-7 under the genus Roseolovirus, rather than HHV-5 (under the genus Cytomegalovirus). ese data suggested that the PCMV can be classified as a member of the genus Cytomegalovirus under the subfamily Betaherpesvirinae using DPOL gene (Figure 1), which is in accordance with the phylogenetic tree based on the gB gene [25].…”
Section: Dpol Gene Analysissupporting
confidence: 82%
“…Phylogenetic analysis based on the complete DPOL gene nucleotide sequences demonstrated that all the PCMV isolates share very close relationship, belonging to the same cluster together with HHV-6 and HHV-7 under the genus Roseolovirus, rather than HHV-5 (under the genus Cytomegalovirus). ese data suggested that the PCMV can be classified as a member of the genus Cytomegalovirus under the subfamily Betaherpesvirinae using DPOL gene (Figure 1), which is in accordance with the phylogenetic tree based on the gB gene [25].…”
Section: Dpol Gene Analysissupporting
confidence: 82%
“…Similar to the coinfection of humans with immunosuppressive viruses, the infection of animals with immunosuppressive viruses, followed by secondary viral and bacterial infections, can cause serious harm and inhibit disease prevention and treatment. In a previous study in Sichuan Province, China, we observed that the PCMV and PRRSV coinfection rate in pig was 34.7%, while the PCMV/PRRSV/Thermoproteus tenax virus 1/ pseudorabies virus coinfection rate was 14.9% [30].…”
Section: Discussionmentioning
confidence: 80%
“…Although our previous study confirmed that PCMV suppresses the immune function of porcine central immune organs, there has been little research on the molecular mechanism behind PCMV immunosuppression. The miRNA transcriptome of porcine continuous cell lines was previously reported, but there have been no reports on the miRNA transcriptome of PCMV-infected vital organs [22,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of clinical testing, some PCMV/PRV-infected animals were co-infected with porcine reproductive and respiratory syndrome virus (PRRSV), transfusion transmitted virus (TTV1), and pseudorabies virus (PRV). In addition, Streptococcus, Haemophilus parasuis, Actinobacillus, and Pasteurella suis infections often occur following PCMV/PRV infection, making prevention and treatment more difficult [177]. A transcriptome analysis of PCMV/PRV -infected thymuses showed an up-and downregulation of immune-regulatory genes [178].…”
Section: Pathogenicitymentioning
confidence: 99%